Chimney Filter Model Wet Scrubber to Reduce Air Pollutant Emissions on the Incinerator - Hurip Jayadi; Frida Hendrarinata; Beny Suyanto; Sunaryo Sunaryo (Health Notions, 2021)
In general, inpatient health care facilities produce infectious and non-infectious waste 0.3 mᶟ / day. Non-infectious waste that is burned in an incinerator without a chimney filter, can cause particles, CO, SO2, NOx (air pollutants) and cause environmental pollution. This study aims to make a chimney filter design with a Scrubber model on an incinerator at the Public Health Center, Maospati District, Magetan Regency to reduce the amount of air pollutants emitted. This type of research is experimental research. This research designed a particle trapping device, gas by spraying water into the scrubber. The independent variable of this research was the variation of the water flow sprayed in the scrubber (3.2 liters / minute, 4 liters / minute, 5.6 liters / minute). The dependent variables of this study were particles, SO2, NOx, CO. Data collection using a digital gas detector method in the form of a UV spectrophotometer. Data were analyzed descriptively, in the form of frequency distribution, and percentage, presentation of data in a table based on air emission quality standards from thermal waste processing. The results illustrate that the use of a chimney scrubber filter with water spraying 3.2 liters / minute, 4 liters / minute, 5.6 liters / minute can reduce air pollutants, emission of SO2, CO to below the air quality standard. In addition, this tool can also reduce NOx gas and particles, but not yet below the quality standard. The conclusion from the results of this study is particulate emission air pollutants, gas SO2, CO, NOx. the incinerator can be lowered by modifying variations by spraying water 3.2 liters / minute, 4 liters / minute, 5.6 liters / minute on the chimney scrubber filter on the incinerator. Keywords: incinerator; scrubber; water discharge variations; particle; gas